Teacher readiness in implementing the teaching of design and technology and Its relationship with self-efficacy and intrinsic motivation - Endot, Zaleha; Jamaluddin, Rahimah; Mohd Ayub, Ahmad Fauzi; Mohd Puad, Mohd Hazwan (Macrothink Institute, 2021)
An important component of an education change begins with readiness among the implementers. Willingness to face change needs to be measured from the perspective of the individual implementing the change, especially teachers. Therefore, this study was conducted to identify the relationship between teachers’ readiness in implementing the teaching of Design and Technology (RBT) year four of the Primary School Standard Curriculum (KSSR) with self -efficacy and intrinsic motivation. This study is guided by the Wallace Reflective Model. The quantitative study of this descriptive survey involved 368 teachers of RBT fourth year KSSR subjects in Peninsular Malaysia. Cluster and simple random sampling were used to select the sample for this study. The research instrument consisted of a set of questionnaires containing 77 items. The findings of the study showed that the overall mean of teachers' readiness in terms of reasoning knowledge and PBS skills was high. The readiness of teachers in terms of PBS skills recorded a higher mean value (M = 3.92) compared to reasoning knowledge (M = 3.82). These findings give the impression that teachers are more prepared in terms of PBS skills in implementing the teaching of RBT KSSR. The results of the Pearson Correlation Test showed that there was a moderately positive relationship between the independent variables (self-efficacy and intrinsic motivation) with teachers' readiness. The findings of this study prove that the component of teachers’ readiness is very important to be taken into account in the formulation of a new curriculum. Factors of self-efficacy and intrinsic motivation also need to be considered because these two variables have a significant relationship with the readiness of teachers in implementing teaching in the classroom. Therefore, this study is expected to provide guidance to policy makers and curriculum planners to pay attention to the aspect of teacher readiness when introducing new subjects.